2021
DOI: 10.1016/j.sopen.2020.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Restorative reconstruction after total mesorectal excision for rectal cancer is associated with significant bowel dysfunction from initial presentation

Abstract: Background Patients often desire restorative reconstruction following total mesorectal excision. Reconstruction has become synonymous with providing high-quality rectal cancer care. However, the bowel functional outcomes of restoration from presentation are unknown. We aimed to evaluate the bowel functional effects of rectal cancer treatment from presentation through surveillance. Methods This was a retrospective cohort study from 2014 to 2019 using prospectively collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…Our prior work in the rectal cancer population found no difference in bowel function from presentation to after neoadjuvant therapy. However, there was a significant worsening of incontinence, social impact and need for medication scores after restoration of continuity and at surveillance [14]. This cannot be explained by differences in radiation patterns and doses for anal canal SCC and rectal cancer.…”
Section: Discussionmentioning
confidence: 93%
“…Our prior work in the rectal cancer population found no difference in bowel function from presentation to after neoadjuvant therapy. However, there was a significant worsening of incontinence, social impact and need for medication scores after restoration of continuity and at surveillance [14]. This cannot be explained by differences in radiation patterns and doses for anal canal SCC and rectal cancer.…”
Section: Discussionmentioning
confidence: 93%
“…The results demonstrated that restorative reconstruction was associated with significant worsening of bowel function compared to baseline bowel function that persists at six-months after ileostomy reversal. The authors concluded that restorative reconstruction after total mesorectal excision is associated with worsening of bowel dysfunction when compared to baseline that is persistent [ 35 ].…”
Section: What Studies Have Been Done In Crsmentioning
confidence: 99%
“…[98][99][100][101] Moreover, longitudinal patient-reported outcome tracking for people treated for rectal cancer is vital to understand changes in bowel function and other things that matter most for patients. 102 One mechanism to measure high-quality consultation could be to develop and add a patient-reported outcome regarding communication and decision making into the National Accreditation Program for Rectal Cancer. Taken together, this additional data could lead to development of best practices in shared decision making for rectal cancer to include standardized patient information sources that can be tailored for individual learning styles, clinical, social, and functional factors; surgeon communication training; and mechanisms to evaluate and improve on this process.…”
Section: What Further Data Is Needed?mentioning
confidence: 99%
“…98 99 100 101 Moreover, longitudinal patient-reported outcome tracking for people treated for rectal cancer is vital to understand changes in bowel function and other things that matter most for patients. 102…”
Section: What Further Data Is Needed?mentioning
confidence: 99%
See 1 more Smart Citation